Analisis Penetapan Harga Pokok Produksi Meubel Menurut Ekonomi Islam Di Kecamatan Taman Rajo - Renaldi Pratama; Elyanti Rosmanidar; Khairiyani Khairiyani (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
The aim of this research is to find out how the basic price of furniture production is determined and constrained by Islamic economics in Taman Rajo District. This type of research is descriptive qualitative with primary and secondary data types. The data collection technique in this research uses observation, interview and documentation techniques, while for data analysis the researcher uses domain, textonomic and componential analysis. The results of the research explain that determining the basic price of furniture production according to Islamic economics in Taman Rajo District is carried out using several methods, including furniture business actors in Taman Rajo District determining or calculating the cost of raw materials used to produce furniture products. Business actors calculate labor costs which are calculated based on the results of the products produced and business actors calculate overhead costs which are costs incurred apart from raw material costs and labor costs in the production process. Obstacles in determining the basic price of furniture production according to Islamic Economics in Taman Rajo District include limited business capital which has an impact on determining production prices because the supply of raw materials is less affordable due to limited business capital for furniture business owners. Apart from that, the obstacle in determining the cost of production is that the strategic market target has not been achieved because the marketing strategy implemented by the business owner has not been maximized so that determining the cost of production is still based on the number of customers who order furniture products.